Reimagining India’s Skill Ecosystem for Viksit Bharat @2047: Policy, Infrastructure, and Inclusive Growth (Journal of Advances and Scholarly Researches in Allied Education, 2025)
India’s skill development ecosystem is undergoing a transformative shift to meet the demands of a rapidly evolving economy. The paper examines the current state of vocational training, industrial collabouration, and policy frameworks while identifying gaps and opportunities for innovation. Key themes include integrating education with skills, fostering industry partnerships, reforming apprenticeships, and ensuring equitable access for marginalized communities. The study highlights successful models like Project Aadika, which empowered tribal women through skill-based micro-enterprises, and proposes actionable strategies for a future-ready workforce. Using a mixed-methods approach, the research evaluates policy effectiveness, infrastructure readiness, and emerging trends such as AI and green skills. The findings emphasize the need for decentralized, demand-driven skilling models aligned with local economic realities.